Towards a need for the code of professional governance in policies making and management for public sector: the Malaysian experience - Mohamad Yunus, Mohamad Ismail (Thomson Reuters Malaysia Sdn. Bhd, 2017)
Codes of Professional conduct have to be viewed positively as a guide in developing relationships with the clients. While it is expedient to have an Act of Parliament that regulates the particular professional discipline, that same regulatory board cannot replace the need for a professional body that can represent completely the interests of its members. The regulatory board may fall short of developing advances in research and development, in marketing and promotion, and in motivating young and passionate entrants into the professions. In the face of globalization, liberalization and competition, the professional as a body must be able to respond in the best interests of its clients, and the larger national interests. This can only succeed if the professional body has good governance structures in place that would allow for continuing dialogue with the government and civil society and further enrichment of its members through the concept of Maqasid al-Shariah (objectives of Islamic law) and the observance of the principles of Wasatiyyah (moderation). The constitution of the professional body must embody provisions that promote good governance and embrace values of integrity and accountability, and seek support from the public and the government of the day to provide an independent view on all matters. The universal truth is that everything should be done in the public good. Professionals form the backbone of human infrastructure in any economy, politics, social and legal growth. Their contributions through professional performance enhances the good delivery system that facilitates in policies making and management for public sector. They provide the skills and talent in balancing the pursuits of maximization of services. The expression “good governance” has been constantly used lately in both public sector as well as private sector in Malaysia. In the context of a private body it should be within the framework of the statute, which governs the body and also its constitution. In the public sector, it means that the administrators should act professionally and not to abuse or misuse the power or authority given to them. They are regarded as the trustees of the public at large. The scope of this article is on good public governance in the public sector or to be exact, good governmental administration as interpreted by the judiciary especially through its judicial review power.